KONSTRUKSI INTEGRASI AL-QUR’AN-TAREKAT- SAINS DALAM KURIKULUM PESANTREN AL-QUR’AN - Fauzi, Moh; Sulistiyono, Sulistiyono; Kuswandi, Iwan (Universitas Al-Amien Prenduan, 2023)
This study wants to cover of the implementation the character education in one of Tahfidh al-Qur’an Islamic Boarding School. It is located in Ma’had Tahfidh Al-Qur’an (MTA) Pondok pesantren Al-Amien Prenduan Sumenep. The research focus is about how the construction of Al-Qur'an-Tarekat-Science Integration and its implementation in Ma’had Tahfidh Al-Qur’an Al-Amien Prenduan? This research method uses a qualitative approach, with a case study type. The data analysis used qualitative analysis, with the research location at the Al-Amien Prenduan Islamic boarding school, Sumenep, Madura, East Java. The conclusion is that the founding of this study is construction of Al-Qur'an-Tarekat-Science Integration and its implementation in Ma’had Tahfidh Al-Qur’an conducted for 24 hours, because the education that is designed based on the student curriculum for 24 hours, by combining the kepondokan (boarding school) program, school and tahfidh al-Qur’an program. In its implantation could be found religious and smart character, it is conducted on the implementation midnight prayer (Tahajjud) and group prayer (Shalat Jama’ah) and the culture of reading salawat Fatih. Meanwhile the honest character, is designed of the implementation examination either writing, oral, or memorizing the holy Qur’an. The tolerance character and friendship thought the life in student room. And discipline character thought student organization, RTMA.